INTERCULTURAL COMMUNICATION STRATEGIES FOR SUSTAINABLE CONFLICT RESOLUTION IN INDONESIA - Farid, Ahmad Salman; Hakimi, Musawer (KOMUNIKE: Jurnal Komunikasi Penyiaran Islam, 2025)
Diversity often triggers multicultural tensions. Conflict resolution frameworks appropriate to the Indonesian context are still rarely studied. This study offers a strategic framework consisting of three steps: increasing cultural awareness and sensitivity, facilitating inclusive dialogue, and collaborative problem-solving. Using a mixed-method approach, this study combines 25 semi-structured interviews with community leaders, mediators, and stakeholders in five conflict-prone provinces, as well as a survey of 312 respondents. The findings show that increasing cultural awareness strengthens mutual respect and reduces stereotypes; inclusive dialogue is effective in bridging social differences; and collaborative problem solving combines traditional approaches (consensus-based deliberation) with modern governance. However, there are still communication gaps between generations and a lack of follow-up mechanisms.